PERCEPTIONS OF UNDERGRADUATE ACCOUNTING STUDENTS OF THE INCORPORATION OF INFORMATION TECHNOLOGY INTO ACCOUNTING EDUCATION - Charles Omane-Adjekum (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
This research aimed to find out accounting students’ perceptions of the integration of Information Technology (IT) in accounting at University of Cape Coast. The study adopted the descriptive survey design. The research included a total sample size of 248 students. Multistage sampling was employed in selecting the sample for the study. Descriptive statistics (means and standard deviation) were used to analyse all the research questions. The research found out that IT integration is relevant in the teaching and learning of accounting at the tertiary level. It was revealed that accounting students are ever ready and prepared to use IT tools in the teaching and learning process. The study recommended that programme designers include courses that will expose students to the various information technology tools, particularly IT tools related to accounting. The academic board should encourage lecturers to integrate IT in the accounting learning process.